Pengaruh Komunikasi Interpersonal dan Disiplin Kerja Terhadap Produktivitas Karyawan (Studi pada Usaha Dagang Sumber Agung) - Ferdy Firdyanto; Imam Baidlowi; Agoes Hadi Poernomo (Transformasi: Journal of Economics and Business Management, 2024)
This study aims to analyze the influence of interpersonal communication and work discipline on employee productivity at UD Sumber Agung trading business. This type of research is quantitative. The population studied was all employees of UD Sumber Agung, totaling 51 employees. The sampling technique used saturated, which means that all members were sampled. Data collection was carried out by distributing questionnaires, and then analyzed using multiple linear regression with the help of the SPSS version 25 program. The hypothesis testing used was the partial significance test (t test) and the simultaneous significance test (f test). The results of the study concluded that: (1) interpersonal communication has a significant negative effect on employee productivity at UD Sumber Agung. (2) Work discipline has a significant negative influence on the productivity of UD Sumber Agung employees. And (3) interpersonal communication and work discipline together have a significant influence on the productivity of UD Sumber Agung employees.